Cultural Media Between The Preservation Of Identity And The Waves Of Cultural Imperialism - رقاب محمد, (International Journal of Social Communication, 2019)
This paper aims primarily to address cultural media, and the role it plays in preserving the social fabric, and relations between individuals and between individuals and institutions on the other. And in light of the development of means of communication, it became clear that the relationship of culture and information are new variables and we will try to identify the concept of cultural media, and of the issues and the most important definitions. Highlighting the role of the media in dealing with cultural issues.